Clinical significance of the histopathological metastatic largest lymph node size in colorectal cancer patients - Omeroglu, Sinan; Gulmez, Selcuk; Uzun, Orhan; Senger, Aziz Serkan; Bostanci, Ozgur; Guven, Onur; Polat, Erdal; Duman, Mustafa (Frontiers in Oncology, 2023)
Background:The metastatic lymph nodes (MLN) are interpreted to be correlated with prognosis of the colorectal cancers (CRC). The present retrospective study aimed to investigate the clinical significance of the largest MLN size in terms of postoperative outcomes and its predictive value in the prognosis of the patients with stage III CRC. Methods:Between May 2013 and December 2018, a total of 101 patients who underwent curative resection for stage III CRC retrospectively reviewed. All patients were divided into two groups regarding cut-off value (<1.05 cm and ≥1.05 cm) of maximum MLN diameter measured histopathologically. A comparative analysis of demographic and clinicopathological characteristics of the patients and their postoperative outcomes were performed. Results: Two groups carried similar demographic data and preoperative laboratory variables except the lymphocyte count, hematocrit (HCT) ratio, hemoglobin level and mean corpuscular volume (MCV) value (P<0.05). The patients with MLN diameter ≥1.05 cm (n=46) needed more erythrocyte suspension and were hospitalized longer than the patients with a diameter <1.05 cm (n=55) (P=0.006 and 0.0294, respectively). Patients with MLN diameter < 1.05 cm had a significantly longer overall survival than patients with MLN diameter ≥ 1.05 cm (75,29 vs 52,57 months, respectively). Regarding the histopathologic features, the patients with MLN diameter ≥1.05 cm had larger tumor size and higher number of MLN than those with diameter <1.05 cm (P=0.049 and 0.001). Conclusion:The size of MLN larger than 1.05 cm may be predictive for a poor prognosis and lower survival of stage III CRC patients. The largest MLN size may be a proper alternative factor to the number of MLNs in predicting prognosis or in staging CRC patients. Keywords: Colorectal cancer, Lymph node metastasis, Lymph node size